TEACHER PERFORMANCE IN VIEW OF COMPETENCE, DISCIPLINE AND WORK MOTIVATION (Study on SMP Negeri 1 Wonosari Klaten) - Latifa Kusuma Wardani; Istiatin Istiatin; Sri Hartono (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This research was conducted to determine and analyze the effect of competence, discipline and motivation on the performance of teachers at SMP Negeri 1 Wonosari Klaten. This research was conducted at SMP Negeri 1 Wonosari Klaten. Quantitative approach used in this research. The population in this study were all teachers at SMP Negeri 1 Wonosari Klaten. The number of samples is 45 people. The sampling technique uses the census sampling method. Data collection using a questionnaire technique. Data analysis techniques used statistical analysis, namely the classical assumption test, multiple linear regression test, F test, t test, and the coefficient of determination (R2). The results of the study show that partially competence has a significant effect on teacher performance at SMP Negeri 1 Wonosari Klaten. Partially, discipline has a significant effect on teacher performance at SMP Negeri 1 Wonosari Klaten. Partially, motivation has a significant effect on teacher performance at SMP Negeri 1 Wonosari Klaten. The test results for the coefficient of determination obtained an Adjusted R2 value of 0.463 or 46.3% indicating that the performance of SMP Negeri 1 Wonosari Klaten teachers is influenced by competency, discipline and motivation variables, while the remaining 53.7% is explained by other variables. Keywords: Teacher Performance, Competence, Disciplin, Motivation